Interruptions and Silences in Conversations: A Turn-Taking Analysis - Lestary, Agustina; Krismanti, Ninuk; Hermaniar, Yulieda (PAROLE: Journal of Linguistics and Education, 2017)
This study is set to investigate the purposes behind interruptions and the meanings of silences in conversations. The data are taken from three casual conversations among friends. To analyze the data, the recorded conversations are first transcribed based on Jefferson’s the Glossary of Transcript Symbols (Jefferson, 2004). The transcribed conversations are analyzed using turn-taking approach in Conversation Analysis. To interpret the results of analysis, inferential method is applied. As the findings, the writers find that speakers interrupt for two purposes: to complete turns and to cut them. To go deeper, speakers interrupt when they have shared knowledge and/or similar perspective on something. In terms of silence, the meanings behind it are highly dependent on what are uttered prior to or after the occurrence of silence. Silences can indicate topic switch, speaker’s wish to continue the same topic, and disagreement. In a conversation, silences lead to awkward situations among speakers and show troubles in conversation flows.